1988
DOI: 10.1128/jb.170.4.1913-1919.1988
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the iron uptake region of the Vibrio anguillarum plasmid pJM1: molecular cloning of genetic determinants encoding a novel trans activator of siderophore biosynthesis

Abstract: Clones carrying the iron uptake region of the Vibrio anguillarum plasmid pJM1 were subjected to insertion mutagenesis, using transposon Tn3::HoHo1 which carries a promoterless lacZ gene and can thus generate lacZ transcriptional fusions if inserted downstream from an indigenous promoter. Four classes of insertion mutants were obtained based on the level of expression of components of the iron uptake system, and six genetic units were defined according to the phenotype of the mutants. Five of the six genetic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
126
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 27 publications
6
126
0
Order By: Relevance
“…The library was constructed using pVK102 and 8399 chromosomal DNA partially digested with HindIII as described previously (Genti-Raimondi et al, 1991). The Tn3-HoHo1 transposon (Stachel et al, 1985) was used as described previously (Tolmasky et al, 1988) to generate insertional derivatives of recombinant cosmids harbouring A. baumannii 8399 DNA. Recombinant cosmids and Tn3-HoHo1 insertional derivatives were introduced into E. coli DH5α by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…The library was constructed using pVK102 and 8399 chromosomal DNA partially digested with HindIII as described previously (Genti-Raimondi et al, 1991). The Tn3-HoHo1 transposon (Stachel et al, 1985) was used as described previously (Tolmasky et al, 1988) to generate insertional derivatives of recombinant cosmids harbouring A. baumannii 8399 DNA. Recombinant cosmids and Tn3-HoHo1 insertional derivatives were introduced into E. coli DH5α by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…1). Genetic studies utilizing transposon (Tn3::HoHo1) insertion mutagenesis have demonstrated that mutations in fatD, -C, or -B affected FatA expression, suggesting an operon organization of these genes (6,8). A further regulatory linkage between iron transport genes and anguibactin biosynthetic genes has also been proposed since insertion mutations in the iron transport genes led to lowering or complete shutoff of anguibactin biosynthesis (8).…”
mentioning
confidence: 99%
“…The positive regulation is mediated by the plasmid-encoded 110-kDa AngR protein whose gene lies immediately downstream of fatA and by trans acting factors encoded in a region located noncontiguous to the iron uptake region in the pJM1 plasmid (5,8,9,10). The negative regulation is afforded by the chromosomally encoded Fur protein (11,12) and by an antisense RNA (RNA␣) (13).…”
mentioning
confidence: 99%
“…Three pJM1-encoded proteins, p40, pOM2, and pAngR, have been shown to be iron regulated and required for iron uptake (3,10,12,29,31), but direct demonstrations that they are also required for virulence of V. anguillarum 775(pJM1) are lacking. This is due in part to the difficulties encountered when attempting to introduce plasmid DNA into V. anguillarum 775(pJM1) in the presence of an apparent pJM1-mediated restriction or exclusion system (6a).…”
mentioning
confidence: 99%